2014
DOI: 10.1111/bjh.13116
|View full text |Cite
|
Sign up to set email alerts
|

A modified scoring of the NCCNIPI is more accurate in the elderly and is improved by albumin and β2‐microglobulin

Abstract: SummaryThe International Prognostic Index (IPI) has been used for decades in diffuse large B-cell lymphoma (DLBCL). A retrospective cancer registry analysis in North America showed significantly improved results when an enhanced IPI, the National Comprehensive Cancer Network (NCCN)-IPI was applied. This novel score puts more weight on age and high levels of lactate dehydrogenase (LDH). Nevertheless, it remains unclear if these results can be extrapolated to the general population. This retrospective bicentre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 14 publications
3
62
1
2
Order By: Relevance
“…In our series, the comparisons between NCCN‐IPI and IPI with the reclassification calibration statistics indicated that NCCN‐IPI had better discriminatory power. This was also the case in the Austrian series (Melchardt et al , ), in which the NCCN‐IPI has been validated, showing a better discriminatory capacity than the IPI and identifying a very bad outcome group with a 5‐year OS of 32·3%. However, the IPI also separated the high‐risk group with a 5‐year OS rate of 40%.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our series, the comparisons between NCCN‐IPI and IPI with the reclassification calibration statistics indicated that NCCN‐IPI had better discriminatory power. This was also the case in the Austrian series (Melchardt et al , ), in which the NCCN‐IPI has been validated, showing a better discriminatory capacity than the IPI and identifying a very bad outcome group with a 5‐year OS of 32·3%. However, the IPI also separated the high‐risk group with a 5‐year OS rate of 40%.…”
Section: Discussionmentioning
confidence: 63%
“…This gave rise to the NCCN‐IPI, with a maximum score of 8 points (Table ), which determined four risk groups with significantly different 5‐year OS. The NCCN‐IPI improved the discrimination of the LR and HR groups with, respectively, 96% and 33% of 5‐year OS rates, and was validated in an independent series of 1138 patients from the BCCA and also in an Austrian series of 499 patients treated with R‐CHOP (Melchardt et al , ). However, a population‐based Danish/Canadian series of 434 patients staged with positron emission tomography/computed tomography (PET/CT) (El‐Galaly et al , ) was not able to reproduce the NCCN‐IPI exactly, and although it distinguished four risk groups it did not identify a very high‐risk group.…”
Section: Variables and Scoring Of The Different Systems (Ipi Nccn‐ipmentioning
confidence: 99%
“…The enhanced NCCN-IPI index improved on the IPI specification by dividing age into four categories (B40, 40-60, 60-75, and[75 years), LDH elevation into two levels (1-3 times, and [3 times upper limit of normal), and by identifying high-risk extranodal sites of involvement [8]. This new clinically useful index has been validated in a separate British Columbia Cancer Agency population-based database as part of the original study, showing higher CPE than the IPI (77 vs. 74 %), and confirmed its superiority in other subsequent DLBCL series (for example, CPE was 75 vs. 70 % in the study by Mian et al [21][22][23][24]). Specific anatomical sites of lymphoma origin also have a prognostic value and may derive heterogeneous benefits from immunochemotherapy [10,16].…”
Section: Discussionmentioning
confidence: 66%
“…This is a clinical factor that has been shown to be prognostic in HL as well as non-Hodgkin lymphomas. [32][33][34][35][36][37][38] However, the small number of patients and relative heterogeneity of therapy limit conclusions regarding prognostication.…”
Section: Confirm That Cytomorphology Is Compatible With Gzlmentioning
confidence: 99%